2021
DOI: 10.3390/jcm10132836
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Severity of Inflammatory Changes in Chronic Sinusitis and the Level of Vitamin D before and after the FESS Procedure

Abstract: There have been a few reports confirming that vitamin D (VD3) deficiency increases inflammation in the paranasal sinuses. The work brings new information that, despite the presence of inflammation before surgery, patients with higher vitamin D levels had less inflammation, and this has been proven on three levels. We show that vitamin D levels clearly correlate with the severity of the disease in chronic sinusitis. These results have been confirmed in imaging studies (Lund MacKay scale), endoscopy (Lund-Kenned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Zand et al described a negative correlation with SNOT-22, the Lund-Mackay score, and serum vitamin D levels, with mean vitamin D levels of 24.6 ± 16.9 ng/mL [ 13 ]. Likewise, Kalinczak et al demonstrated that levels of vitamin D in group 1 were 28.02 ng/mL, while in group 2, they were 23.01 ng/mL [ 15 ]. Tomaszewska et al revealed a positive correlation with Lund-Mackay scores (R = -0.42) and a negative correlation with SNOT-22 scores (R = -0.3)m while the levels of vitamin D reported were 28.4 ng/mL in CRS without nasal polyps and 21.0 ng/mL in CRS with nasal polyps, whereas in control groups, the levels were 30.9 ng/mL [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Zand et al described a negative correlation with SNOT-22, the Lund-Mackay score, and serum vitamin D levels, with mean vitamin D levels of 24.6 ± 16.9 ng/mL [ 13 ]. Likewise, Kalinczak et al demonstrated that levels of vitamin D in group 1 were 28.02 ng/mL, while in group 2, they were 23.01 ng/mL [ 15 ]. Tomaszewska et al revealed a positive correlation with Lund-Mackay scores (R = -0.42) and a negative correlation with SNOT-22 scores (R = -0.3)m while the levels of vitamin D reported were 28.4 ng/mL in CRS without nasal polyps and 21.0 ng/mL in CRS with nasal polyps, whereas in control groups, the levels were 30.9 ng/mL [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
“…When treatment begins, 25 vitamin D3 is converted to 1.25 vitamin D3, and cathelicidin, an antimicrobial peptide, is produced. The acute-phase reaction is inhibited by vitamin D3, and inflammation resulting from CRS may cause vitamin D3 levels to drop [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…The proliferation of Th2 cells leads to an increase in interleukin 31 (IL-31) synthesis, an effector cytokine that plays an important role in the pathogenesis of atopic and allergic diseases [ 25 , 26 ]. Given these correlations, a significant correlation between vitamin D deficiency and inflammation in patients with chronic rhinosinusitis with and without nasal polyps is shown [ 27 , 28 , 29 , 30 ].…”
Section: Vitamin D3mentioning
confidence: 99%
“…Cal inhibits in ammation, oxidative stress and immune responses. There have been many publications con rming that chronic in ammatory diseases are associated with reductions in vitamin D levels 9 . Additionally, the administration of vitamin D compounds at doses near the upper limit of safety may serve to maximize immune health bene ts and mitigate in ammation and disease severity in patients with SARS-CoV-2 infections 10 .…”
Section: Introductionmentioning
confidence: 99%